PENGARUH PENDAPATAN ASLI DAERAH TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN/KOTA PROVINSI BANTEN - Pindonta Nalsal; Rochhaeni Rochhaeni; Nena Nurmala Diana (The Asia Pacific Journal Of Management Studies, 2017)
This study aims to determine the Effect of Regional Original Income on Economic Growth in the Regency / City of Banten Province in 2012-2015. In this study the independent variable is Regional Original Income (PAD), while the dependent variable is Economic Growth.The data used in this study are secondary data obtained from the Central Statistics Agency. With the data used, namely the financial overview and also the Gross Regional Domestic Product (GRDP), which is to determine the annual economic growth rate in the 2012-2015 observation period. The data analysis technique in this study used the Normality Test, Simple Regression Equation Test, Correlation Coefficient Test, Determination Analysis, and Significant Analysis (t test).The results of this study indicate that it is known that the result of tcount is the result of tcount of 654 and ttable 1,697 (attached). For the level of error α = 0.05 and df = 32-2 (df = 30), then based on table t in the attachment, the ttable value is 1.697, thus compared to tcount <ttable (654 <1.697) so that it falls in the rejection area H0 (H1 is accepted and H0 is rejected). And based on the significance value of the output of SPSS sig.0.0518 <0.05 means that it is influential but not significant. This means that the research on Regional Original Income (PAD) has an effect on Economic Growth but is not significant.